(untitled) (Orfeu, 2021)
Seeking to contribute to the studies of Harmony, we propose a data collection, with commentaries, of primary expressions of Greek musical literature, from Aristoxenus of Tarentum (4th century BC). Moreover, through that semantic analysis, we aim to understand the organization of his treatise on Harmony, highlighting its parts and methodology. Consequently, we point out some philosophical principles from musical thoughts, such as the mandatory critical-poetic posture of the μουσῐκός (mousikós) and the knowledge of the musical episteme. Thus, we include shorts comments on the tradition of the musical literature in Latin, found in authors such as Martianus Capella and Fabius Fulgentius, approximately in the 5th century AD, to later theorists, with Sethus Calvisius and Blanchinus Veronensis, already in the early 17th and 18th centuries respectively, all heirs of Aristoxenus and his epigones, in mention of Aristides Quintilian, Cleonides and Ptolemy.